Transcriptomic analysis of fruit stored under cold conditions using controlled atmosphere in Prunus persica cv. “Red Pearl” - Sanhueza, Dayan; Vizoso, Paula; Balic, Iván; Campos-Vargas, Reinaldo; Meneses, Claudio (Frontiers in Plant Science, 2015)
Cold storage (CS) can induce a physiological disorder known as chilling injury (CI) in nectarine fruits. The main symptom is mealiness that is perceived as non-juicy fruit by consumers. Postharvest treatments such as controlled atmosphere (CA; a high CO2 concentration and low O2) have been used under cold conditions to avoid this disorder. With the objective of exploring the mechanisms involved in the CA effect on mealiness prevention, we analyzed transcriptomic changes under six conditions of ‘Red Pearl’ nectarines by RNA-Seq. Our analysis included just harvested nectarines, juicy non-stored fruits, fruits affected for CI after CS and fruits stored in a combination of CA plus CS without CI phenotype. Nectarines stored in cold conditions combined with CA treatment resulted in less mealiness; we obtained 21.6% of juice content compared with just CS fruits (7.7%; mealy flesh). RNA-Seq data analyses were carried out to study the gene expression for different conditions assayed. During ripening, we detected that nectarines exposed to CA treatment expressed a similar number of genes compared with fruits that were not exposed to cold conditions. Firm fruits have more differentially expressed genes than soft fruits, which suggest that most important changes occur during CS. On the other hand, gene ontology analysis revealed enrichment mainly in metabolic and cellular processes. Differentially expressed genes analysis showed that low O2 concentrations combined with cold conditions slows the metabolic processes more than just the cold storage, resulting mainly in the suppression of primary metabolism and cold stress response. This is a significant step toward unraveling the molecular mechanism that explains the effectiveness of CA as a tool to prevent CI development on fruits.